2013
DOI: 10.1152/jn.00879.2012
|View full text |Cite
|
Sign up to set email alerts
|

Optical imaging of cortical networks via intracortical microstimulation

Abstract: Brock AA, Friedman RM, Fan RH, Roe AW. Optical imaging of cortical networks via intracortical microstimulation. J Neurophysiol 110: 2670 -2678. First published September 11, 2013 doi:10.1152/jn.00879.2012.-Understanding cortical organization is key to understanding brain function. Distinct neural networks underlie the functional organization of the cerebral cortex; however, little is known about how different nodes in the cortical network interact during perceptual processing and motor behavior. To study cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 64 publications
6
40
0
Order By: Relevance
“…In an optical imaging study that examined the pattern of activation following focal electrical stimulation, local patchy activations were observed, similar in size and distribution to anatomically labeled patches following a focal tracer injection. These activation patterns were, moreover, relatively consistent following cortical stimulation at different laminar depths (15). In a 2-photon study that examined neuronal activation in response to electrical stimulation (typically less than 10 μA), the authors reported that the activated subpopulation (<300 μm zone) remained within the activation focus but that the subpopulation within the locus shifted, suggesting that the stimulated network was not randomly distributed.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In an optical imaging study that examined the pattern of activation following focal electrical stimulation, local patchy activations were observed, similar in size and distribution to anatomically labeled patches following a focal tracer injection. These activation patterns were, moreover, relatively consistent following cortical stimulation at different laminar depths (15). In a 2-photon study that examined neuronal activation in response to electrical stimulation (typically less than 10 μA), the authors reported that the activated subpopulation (<300 μm zone) remained within the activation focus but that the subpopulation within the locus shifted, suggesting that the stimulated network was not randomly distributed.…”
Section: Discussionmentioning
confidence: 91%
“…Such methods have been developed in conjunction with intrinsic signal optical imaging (13-16), voltage sensitive dye imaging (17-19), and fMRI (20-22) following single site stimulation. These methods have revealed both local intra-areal and distant inter-areal connection patterns (15, 23). …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the use of focal electrical stimulation with optical imaging to map intra-areal or inter-areal connections. 27,28 However, the mapping of more global connections is better conducted with functional MRI (fMRI) methods, an approach that lacks the spatial resolution of intrinsic optical imaging but has the important advantage of being able to resolve changes in subsurface structures. Indeed, the potential for using light-based methods with fMRI for functional tract tracing has already been demonstrated.…”
Section: Ins As a Functional Tract Tracing Methodologymentioning
confidence: 99%
“…In primates, the retinotopic organization of neurons is mirrored between each adjacent visual cortical area (Engel et al, 1994(Engel et al, , 1997DeYoe et al, 1996). In tree shrews, the retinotopic organization of area V1 has been characterized using intrinsic optical imaging techniques, but no maps could be obtained for extrastriate areas (Bosking et al, 2000(Bosking et al, , 2002. Unlike primates where the border between V1 and V2 occurs at the vertical meridian of the visual field, the transition between the two areas in tree shrew visual cortex takes place at 15°i n the ipsilateral visual field.…”
Section: Retinotopic Organization Of the Tree Shrew Visual Cortexmentioning
confidence: 99%
“…The accuracy of the stereotaxic dLGN location was confirmed by recording multiunit activity in response to contralateral and ipsilateral visual stimulation, because each of the six layers of the dLGN show preference for stimulus increments or decrements, ocular input, and retinotopic position (Conway and Schiller, 1983). Thus, electrodes were positioned in the dLGN to stimulate groups of neurons who's receptive-field locations matched the portion of V1 recorded by optical imaging (Bosking et al, 2000(Bosking et al, , 2002. Although, neurons in the dLGN have small, well defined receptive fields, pulvinar neuron receptive fields are diffuse and difficult to hand-map.…”
mentioning
confidence: 99%